Genetic characterization of trh positive Vibrio spp. isolated from Norway - Bauer Ellingsen, Anette; Olsen, Jaran S.; Granum, Per E.; Rorvik, Liv M.; González-Escalona, Narjol (Frontiers in Cellular and Infection Microbiology, 2013)
The thermostable direct hemolysin (TDH) and/or TDH-related hemolysin (TRH) genes are carried by most virulent Vibrio parahaemolyticus serovars. In Norway, trh+ V. parahaemolyticus constitute 4.4 and 4.5% of the total number of V. parahaemolyticus isolated from blue mussel (Mytilus edulis) and water, respectively. The trh gene is located in a region close to the gene cluster for urease production (ure). This region was characterized in V. parahaemolyticus strain TH3996 and it was found that a nickel transport operon (nik) was located between the first gene (ureR) and the rest of the ure cluster genes. The organization of the trh-ureR-nik-ure gene cluster in the Norwegian trh+ isolates was unknown. In this study, we explore the gene organization within the trh-ureR-nik-ure cluster for these isolates. PCR analyses revealed that the genes within the trh-ureR-nik-ure gene cluster of Norwegian trh+ isolates were organized in a similar fashion as reported previously for TH33996. Additionally, the phylogenetic relationship among these trh+ isolates was investigated using Multilocus Sequence Typing (MLST). Analysis by MLST or ureR-trh sequences generated two different phylogenetic trees for the same strains analyzed, suggesting that ureR-trh genes have been acquired at different times in Norwegian V. parahaemolyticus isolates. MLST results revealed that some pathogenic and non-pathogenic V. parahaemolyticus isolates in Norway appear to be highly genetically related.